Alveolar Oxygen Uptake and Blood Flow Dynamics in Knee Extension Ergometry - Hughson, R. L.; MacDonald, M. J.; Shoemaker, J. K.; Borkhoff, C. (Methods of Information in Medicine, 1997)
The relationship was studied between the increase in oxygen uptake (VO2) measured breath-by-breath at the mouth, and the increase in femoral artery blood flow measured continuously with pulsed and echo Doppler methods. Five men exercised at 50 W on a knee extension ergometer in both the supine and the upright posture. The kinetics of the responses were determined by curve fitting to obtain the mean response time (MRT = 63% of the time required to achieve steady state). In the upright position, the increase in blood flow (MRT = 12.4 ± 9.4 s, mean ± SD) was faster than the increase in VO2 (29.6 ± 9.3 s). Likewise in the supine position, blood flow increased more rapidly (25.1 + 9.7 s vs. 36.7 ± 9.6 s). It should be noted that the increase in blood flow appeared to be faster than VO2, yet when blood flow adapted more slowly in the supine posture, it had an impact on the adaptation of VO2. This suggests that blood flow might have important effects on metabolism at the onset of submaximal exercise.
Keywords: Oxygen Uptake; Exercise; Breath-by-Breath Gas Exchange; Pulsed Doppler; Echo Doppler